Implementasi Media Pop-up book dalam Meningkatkan Kedalaman Pemahaman Materi Fiqih pada Siswa MI Muhammadiyah Taraman - Iffah Mukhlisah; Daliman Khoiruddin; Alexandria Treedy Jannatunnisa (Universitas Ngudi Waluyo, 2025)
Abstract This study aims to analyze the effectiveness and implementation process of pop-up book media in increasing the depth of understanding of Fiqh material, especially the Pillars of Hajj, in fourth-grade students of MI Muhammadiyah Taraman. The background of the study is based on the challenges of Fiqh learning which tends to be abstract and textual, making it less effective for students at the concrete operational age who need visual aids and real experiences. The research method used is a mixed-methods with a sequential explanatory design. The quantitative stage used a quasi-experiment with a pre-test and pos-ttest control group design on 28 students. Qualitative data were obtained through interviews, observations, and document studies, then analyzed thematically. The results showed that the implementation of pop-up books significantly improved students' conceptual understanding, with an average posttest score (80.59) exceeding the pretest score (68.07) and the KKM (75). Statistical tests (t-test) confirmed this significant difference (p<0.05). Qualitatively, pop-up books are effective through three mechanisms: visual-spatial effects for long-term memory, physical interactivity that increases student engagement (78% active), and learning differentiation. However, the study also identified technical constraints such as text that was too small, lengthy teacher preparation time, and limited content. In conclusion, pop-up books have proven to be an effective and engaging medium for improving Islamic jurisprudence (Fiqh) understanding at the elementary school (MI) level. Their success depends on appropriate design for children's characteristics, teacher training, and integration with other methods, such as live demonstrations for procedural aspects. Abstrak Penelitian ini bertujuan untuk menganalisis efektivitas dan proses implementasi media pop-up book dalam meningkatkan kedalaman pemahaman materi Fiqih, khususnya Rukun Haji, pada siswa kelas IV MI Muhammadiyah Taraman. Latar belakang penelitian didasari oleh tantangan pembelajaran Fiqih yang cenderung abstrak dan tekstual, sehingga kurang efektif untuk siswa usia operasional konkret yang membutuhkan bantuan visual dan pengalaman nyata. Metode penelitian yang digunakan adalah mixed-methods dengan desain sequential explanatory. Tahap kuantitatif menggunakan eksperimen kuasi dengan pre-test dan post-test control group design pada 28 siswa menggunakan analisis statistik . Data kualitatif diperoleh melalui wawancara, observasi, dan studi dokumen, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa implementasi pop-up book secara signifikan meningkatkan pemahaman konseptual siswa, dengan nilai rata-rata post-test (80,59) melampaui nilai pre-test (68,07) dan KKM (75). Uji statistik (t-test) mengonfirmasi perbedaan yang signifikan ini (p<0,05). Secara kualitatif, pop-up book efektif melalui tiga mekanisme: efek visual-spasial untuk memori jangka panjang, interaktivitas fisik yang meningkatkan keterlibatan siswa (78% aktif), dan diferensiasi pembelajaran. Namun, penelitian juga mengidentifikasi kendala teknis seperti desain teks yang terlalu kecil, waktu persiapan guru yang panjang, dan keterbatasan konten. Kesimpulan, pop-up book terbukti sebagai media yang efektif dan menarik untuk meningkatkan pemahaman Fiqih di tingkat MI. Keberhasilannya bergantung pada desain yang sesuai karakteristik anak, pelatihan guru, dan integrasi dengan metode lain seperti demonstrasi langsung untuk aspek prosedural.